Cross-Sectional Microhardness and Chemical Composition of Primary Teeth with Green Discoloration due to Hyperbilirubinemia - Adriana Furtado Macedo; Michele Baffi Diniz; Ramiro Anthero de Azevedo; Reginaldo Raimundo Fujita (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the chemical components and cross-sectional microhardness of primary teeth with hyperbilirubinemia-induced green pigmentation. Material and Methods: The sample consisted of two anterior and two posterior green primary teeth discolored by bilirubin and regular primary teeth, paired according to child age and tooth type. Scanning energy dispersive spectroscopy was used to investigate the mass percentage of calcium, phosphorus, and carbon, and a microhardness tester was used to assess the cross-sectional microhardness of enamel and dentin. The collected data were analyzed using the Student's t-test and Mann-Whitney (p<0.05). Results: There was a significant decrease in calcium in the dentin of the green discoloration group compared with the control group. Although the differences in cross-sectional microhardness were not significant, all data showed lower microhardness in both enamel and dentin in the green discoloration group. Conclusion: The calcium content in the dentin of green-discolored primary teeth is lower than in regular primary teeth, but the microhardness of enamel and dentin is not affected.